Investigating the effectiveness of lighting in designing outdoor pathways at night دراسة فاعلية الإضاءة في تصميم مسارات الحركة الخارجية ليلاً - Philippe Emad Farid Abdelmessih ; Mohamed El Fayoumi; Ashraf Nessim (Journal of Urban Research)
Outdoor spaces are the fundamental parts of the physical environment, allowing people to engage in a variety of activities and purposes. The shapes and forms of these spaces have always been defined by the landscape elements: the hardscape and the softscape; for instance, outdoor furniture, trees, plantations, and light fixtures. The aim of this research is to investigate the role of artificial lighting in illuminating pathways and how artificial lighting can be used in optical and visual art, emphasizing the importance of pathway lighting design. The study will employ a methodology, beginning with a literature review of data extracted from reports, articles, and academic papers. This will be followed by observational analysis and a survey conducted on the outdoor pathways of the selected case study "Open Air Mall." These methods will facilitate an in-depth investigation of various aspects of artificial lighting for pathways, such as lighting intensity, techniques, pollution, placement, and color temperature. The research seeks to explore the effectiveness of artificial lighting in enhancing the functionality of pathways at night and its role with other landscape elements in guiding users. In the end, the findings will provide insights into designing effective artificial lighting for pathways to optimize their use during the night.